Effectiveness of virtual reality training for balance and gait rehabilitation in people with multiple sclerosis: a systematic review and meta-analysis. - Casuso Holgado, María Jesús; Martín-Valero, Rocío; Carazo, Ana F.; Medrano-Sánchez, Esther M.; Cortés-Vega, María-Dolores; Montero-Bancalero, Francisco José (Sage, 2018)
Objective: To evaluate the evidence for the use of virtual reality to treat balance and gait impairments in multiple sclerosis rehabilitation. Design: Systematic review and meta-analysis of randomized controlled trials and quasi-randomized clinical trials. Methods: An electronic search was conducted using the following databases: MEDLINE (PubMed), Physiotherapy Evidence Database (PEDro), Cochrane Database of Systematic Reviews (CDSR) and (CINHAL). A quality assessment was performed using the PEDro scale. The data were pooled and a meta-analysis was completed. This systematic review was conducted in accordance with the (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) PRISMA guideline statement. It was registered in the PROSPERO database (CRD42016049360). Results: A total of 11 studies were included. The data were pooled, allowing meta-analysis of seven outcomes of interest. A total of 466 participants clinically diagnosed with multiple sclerosis were analysed. Results showed that virtual reality balance training is more effective than no intervention for postural control improvement (standard mean difference (SMD) = −0.64; 95% confidence interval (CI) = −1.05, −0.24; P = 0.002). However, significant overall effect was not showed when compared with conventional training (SMD = −0.04; 95% CI = −0.70, 0.62; P = 0.90). Inconclusive results were also observed for gait rehabilitation. Conclusion: Virtual reality training could be considered at least as effective as conventional training and more effective than no intervention to treat balance and gait impairments in multiple sclerosis rehabilitation.
https://openpolicyfinder.jisc.ac.uk/id/publication/9068
Keywords: Esclerosis múltiple; Fisioterapia - Innovaciones tecnológicas; Virtual reality; postural control; gait; physical therapy; multiple sclerosis